2022
DOI: 10.1097/01.aoa.0000891636.81647.36
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Obstetric Emergency Team Training on Patient Outcome: A Systematic Review and Meta-Analysis

Abstract: (Acta Obstet Gynecol Scand. 2022;101:25–36. doi: 10.1111/aogs.14263) Participants in simulation-based team training in obstetric emergencies often report increased confidence in their ability to manage unfolding emergencies that may present in actual practice. However, empirical data that examines the efficacy of such training on impacting clinical outcomes is incomplete. This review assesses the contribution of simulation-based training for health care providers to the outcomes of obstetric emergencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…The meta-analysis by Brogaard and colleagues, although finding evidence of potential positive effects of obstetric emergency simulation-based team training on risk of neonatal brachial plexus injury (but with a low-certainty level of evidence) and Apgar scores <7, (though this finding failed to achieve statistical significance), found no evidence of a beneficial effect on other outcomes including hypoxic-ischemic encephalopathy. 1 Their findings are similar to other reviews in this area, including a 2020 Cochrane review that concluded multi-professional emergency obstetric training may have positive effects on practical skills, knowledge, and team behavior, but there is little high-certainty evidence of a positive effect on patient outcome. 2 Only 4 of the 21 studies included in Brogaard's metaanalysis were randomized controlled trials, the remainder were retrospective cohort studies.…”
Section: Commentsupporting
confidence: 70%
“…The meta-analysis by Brogaard and colleagues, although finding evidence of potential positive effects of obstetric emergency simulation-based team training on risk of neonatal brachial plexus injury (but with a low-certainty level of evidence) and Apgar scores <7, (though this finding failed to achieve statistical significance), found no evidence of a beneficial effect on other outcomes including hypoxic-ischemic encephalopathy. 1 Their findings are similar to other reviews in this area, including a 2020 Cochrane review that concluded multi-professional emergency obstetric training may have positive effects on practical skills, knowledge, and team behavior, but there is little high-certainty evidence of a positive effect on patient outcome. 2 Only 4 of the 21 studies included in Brogaard's metaanalysis were randomized controlled trials, the remainder were retrospective cohort studies.…”
Section: Commentsupporting
confidence: 70%